Biguanide-transition metals complexes as potential drug for hyperglycemia treatment (2020)
ABSTRACT: Coordination compounds of Cu(ii), Ni(ii), Co(ii), and Zn(ii) with a type of biguanide (known commercially as metformin) have been synthesized and characterized using spectroscopic techniques (FT-IR, UV/VIS), X-ray diffraction techniques and thermal analysis. For all compounds, single crystals were obtained for single-crystal X-ray diffraction. For the first time, an octahedral cobalt compound with the formula [Co(C4H11N5)3]Cl2·2H2O that crystallizes in the monoclinic space group C2/c with one molecule in the asymmetric unit has been obtained. Also, a novel nickel compound with the formula [Ni(C4H11N5) (C4H10N5)]Cl·H2O that crystallizes in the monoclinic space group P21/c with two molecules in the asymmetric unit was obtained. Finally, we obtained copper and zinc compounds that crystallize in the monoclinic space groups P21/n and P21/c with the general formula [Cu(C4H11N5)2]Cl2·H2O and [Zn(C4H12N5)Cl3], respectively. A structural and supramolecular analysis was developed for all compounds using Hirshfeld surface analysis and electrostatic potential maps. The cell viability of the obtained compounds was evaluated in C2C12 (ATCCCRL-1772™) mouse muscle cells and HepG2 (ATCC HB-8065™) human liver carcinoma cells by the MTT assay to determine the potential of the compounds as new safe drugs. The results demonstrate that the compounds exhibit low cytotoxicity at doses less than 250 μg mL-1 with a cell viability greater than 80%.